FREQUENCY OF FEVER AND CEREBROSPINAL FLUID PLEOCYTOSIS IN ACUTE ENCEPHALITIS IN CHILDREN - Nasreen Ali (Army Medical College Rawalpindi, 2021)
Objective: To determine the frequency of fever and cerebrospinal fluid pleocytosis in acute encephalitis in children.